قديم خانقاہی نظام اورسلاسل اربعہ کے بنیادی مشترکات:ایک مطالعہ (Al-Qamar, 2022)
During the Umayyad and Abbasid reigns the mystics tried their best to propagate the teachings of Islam by keeping a distance from the power corridors. They resolved to perform the duty of preaching Islam in a solid and practical way by remaining aloof from the tyrannous governmental powers. Different convoys of the mystics reached every nook and corner of the world in different ages, and with their sincere and compromising policy impressed the veracity of Islam upon the minds of the astray people. And in this way, by enlightening them with the light of Islam, made them a strong link of a wide circle in which the standard of respect and regard is not caste, colour or racial superiority but character and piety. This is the basis of old monastic system. The monastery of Sayed Ali bin Usman Hujveri alias Data Ganj Bakhsh (died 665AH) is considered to be the oldest in the subcontinent (established 431AH). The light of Islam spread in the mountains and valleys of Central Asia through the untiring efforts of the ancient revered saints. The monasteries of the saints acted as the centers of knowledge and enlightenment for many centuries. The fame of the cities like Khiva, Samarkand, Bukhara and Neyshabur spread far and wide. The old monastic system contributed to the propagation of Islam and it created many Orders (Silasil) the fundamental objective of which was to make the following of the teachings of Islam obligatory. Though these orders have differences over the spiritual paths (suluks) they adopt, the root of all the Orders is to ‘enjoin good and forbid evil’. The origin and evolution of these Orders in the subcontinent started in the 13th century. Their number increased rapidly in the beginning, but most of them underwent extinction for different reasons except the four ones. The reason of survival of the Four Orders is the common features of several of their principles.
Keywords: Monastic System; Islam; Main Features; Four Sufi Orders